2003
DOI: 10.1002/ps.623
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of target‐site resistance to ACCase‐inhibiting herbicides in the weed Alopecurus myosuroides (black‐grass)

Abstract: Resistance to aryloxyphenoxypropionate (AOPP), cyclohexanedione (CHD) and phenylurea herbicides was determined in UK populations of Alopecurus myosuroides Huds. Two populations (Oxford AA1, Notts. A1) were highly resistant (Resistance indices 13-->1000) to the AOPP and CHD herbicides fenoxaprop, diclofop, fluazifop-P and sethoxydim, but only marginally resistant to the phenylurea, chlorotoluron. Analyses of acetyl coenzyme A carboxylase (ACCase) activity showed that an insensitive ACCase conferred resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 29 publications
(47 reference statements)
5
46
0
Order By: Relevance
“…So far, six variable amino acids in the ACCase protein may confer different degrees of sensitivity to the herbicides because of difficulties in their access to and/or the fit inside the enzyme active site (Délye et al, 2005;Zhang & Powles, 2006). Furthermore, the high level of resistance verified to sethoxydim is a strong indicator of target site-based resistance because this compound is not exposed to metabolism-based resistance (Moss et al, 2003). As expected, on the ACCase enzyme assay, the RF calculated for the R biotype ranged between 11 and 94 (Table 3).…”
Section: Molecular Studiessupporting
confidence: 58%
See 1 more Smart Citation
“…So far, six variable amino acids in the ACCase protein may confer different degrees of sensitivity to the herbicides because of difficulties in their access to and/or the fit inside the enzyme active site (Délye et al, 2005;Zhang & Powles, 2006). Furthermore, the high level of resistance verified to sethoxydim is a strong indicator of target site-based resistance because this compound is not exposed to metabolism-based resistance (Moss et al, 2003). As expected, on the ACCase enzyme assay, the RF calculated for the R biotype ranged between 11 and 94 (Table 3).…”
Section: Molecular Studiessupporting
confidence: 58%
“…Herbicides from alternative modes of action other than ACCase inhibitors would be recommended strategy to deal with the E. indica resistance. However, caution should be taken to avoid selection pressure from only one herbicide option, because worldwide there have been reported evolved resistant E. indica populations to glyphosate (Ng et al, 2003;Baerson et al, 2002;Kaundun et al, 2011), to metribuzin (Brosnan et al, 2008), and to glufosinate and paraquat (Seng et al, 2010 …”
Section: Molecular Studiesmentioning
confidence: 99%
“…A1, were identified, which were highly resistant to fenoxaprop, diclofop, fluazifop and sethoxydim due to an insensitive ACCase. Genetic studies revealed that the target-site resistance in the two A. myosuroides biotypes was monogenic and nuclear inherited, with the resistant allele showing complete dominance [38].…”
Section: Inhibitors Of Photosystem II (Ps Ii)mentioning
confidence: 99%
“…Black-grass has developed resistance to several types of herbicides, such as phenyl-urea chlorotoluron, acetyl-CoA carboxylase (ACCase), aryloxyphenoxypropionate (AOPP), cyclohexanedione (CHD) and acetolactatesynthase (ALS)-inhibiting herbicides [1,[6][7][8]. The mechanism behind the resistance is reported to be enhanced metabolism in the case of AOPP/CHD resistance [6] and target-site resistance in case of ACCase-inhibiting and ALS-inhibiting herbicides [7,8]. Black-grass is extremely disposed to develop herbicide resistance and there will soon be no effective herbicide left.…”
Section: Introductionmentioning
confidence: 99%